L8 Acute liver failure and hepatitis associated aplastic anaemia: a 17-year single centre experience. (12th September 2022) - Zouzo, Vaia; Jayaprakash, Kavitha; Jagadisan, Barath; Karthikeyan, Palaniswamy; Mtegha, Marumbo; Rajwal, Sanjay
Abstract : Introduction/Background: Hepatitis-associated aplastic anaemia (HAAA) and Acute Liver Failure associated aplastic anaemia (ALF-AA) is a well-recognised but rare disorder with potentially fatal outcome if not treated promptly. The pathogenesis remains unknown. It is characterised by pancytopenia of varying degrees and elevation of aminotransferases. It can result in fulminant liver and or bone marrow failure. Aim: To characterise patients who presented with either HAAA or ALF-AA in Leeds Paediatric Liver Unit and assess response to treatment and outcomes. Subjects and Methods: This was a retrospective study of children who presented to Leeds Paediatric liver Unit with HAAA or ALF-AA between 2004 -2021. All patients had a complete chronic liver disease work up including liver autoantibody screen which was normal. ALF was defined as INR > 2 with or without encephalopathy. Results: We identified 18 children (13 male) with median age 10 years (1.5–15.5 years) (Chart 1). 12 children presented with ALF-AA and six with HAAA. Positive Parvovirus B19 PCR was identified in two cases (one case had HHV6 at the same time). In patients who presented with ALF-AA, 10 developed AA after liver dysfunction, in the remaining two children ALF developed concomitantly with AA. In patients who presented with HAAA, AA preceded hepatitis in one patient, four patients developed both at the same time, and one patient developed AA after hepatitis. Average time between liver dysfunction and AA was 7.6 weeks (1 week – 5 months). In the cohort with ALF-AA (n=12), 9 patients were treated with prednisolone, 6 children achieved normalisation of liver function, although one patient also required tacrolimus. Of those who recovered from liver dysfunction and received steroids (n=6) – two patients needed bone marrow transplant (BMT), two were treated with ATG and the remaining two showed bone marrow recovery. The remaining three patients who did not respond to steroids had a liver transplant (LT) and one required BMT. The three patients with ALF-AA who were not treated with steroids needed LT (2 developed AA post LF; 2 needed BMT and 1 required ATG as well). Of the patients with HAAA (n=6), two achieved normalisation of ALT and bone marrow recovery with prednisolone. In the remaining four children, hepatitis resolved spontaneously, however 2 children had BMT, one is currently listed for BMT, and the other patient died from pneumonia whilst conditioning for BMT. In this cohort three patients out of 18 died (one post BMT and LT due to pulmonary haemorrhage, one whilst conditioning for BMT due to pneumonia, one died within a month of presentation of ALF-AA due to E. coli sepsis). Summary and Conclusion: In our study there was no associated between the severity of liver dysfunction and AA. There may be a beneficial role of steroids in the recovery of the liver, but not necessarily affecting bone marrow recovery or need for BMT. The clinical course and prognosis of AA is independent of liver dysfunction. Early liaison with Paediatric Haematology is essential.